2015
DOI: 10.1091/mbc.e15-03-0181
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the mitochondrial fission protein dynamin-related protein 1 (Drp1) impairs mitochondrial fission and mitotic catastrophe after x-irradiation

Abstract: The role of mitochondrial dynamics in cellular responses to ionizing radiation (IR) is still largely unknown. This study demonstrates that IR triggers Drp1-dependent mitochondrial fission and that Drp1 inhibition attenuates radiation-induced mitotic catastrophe, suggesting that Drp1 is involved in determining the fate of cells after irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…This is because several reports have shown that the overexpression of fusion-related genes such as Mfn1/Mfn2 (Chen et al, 2003) and Opa1 (Frezza et al, 2007) induces mitochondrial elongation in MEFs. In this context, the overexpression of fission-related genes such as Drp1 (Yamamori et al, 2015) and Fis1 (Otera et al, 2010) induces mitochondrial fragmentation in MEFs and HeLa cells, respectively. However, there were only minor changes in the expression levels of Mfn1 and Opa1 during differentiation, and changes in the expression of Fis1 were opposite to the expected results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because several reports have shown that the overexpression of fusion-related genes such as Mfn1/Mfn2 (Chen et al, 2003) and Opa1 (Frezza et al, 2007) induces mitochondrial elongation in MEFs. In this context, the overexpression of fission-related genes such as Drp1 (Yamamori et al, 2015) and Fis1 (Otera et al, 2010) induces mitochondrial fragmentation in MEFs and HeLa cells, respectively. However, there were only minor changes in the expression levels of Mfn1 and Opa1 during differentiation, and changes in the expression of Fis1 were opposite to the expected results.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were only minor changes in the expression levels of Mfn1 and Opa1 during differentiation, and changes in the expression of Fis1 were opposite to the expected results. Actually, FIS1 has been reported to have a weaker effect on mitochondrial fission than DNM1L in MEFs but not in HeLa (Loson et al, 2013; Otera et al, 2010; Yamamori et al, 2015) possibly due to the different mechanisms of mitochondrial morphology regulation in humans and mice. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray irradiation results in DNA damage, abnormal progression through mitosis (mitotic catastrophe), centrosome amplification and formation of micronuclei. In this scenario, incubation with the Drp1 inhibitor Mdivi-1 reduced the centrosome amplification and formation of micronuclei observed after irradiation [99] . Taken together, these results provide clear evidence of a bidirectional link between mitochondria dynamics/ function and cell cycle progression at multiple phases.…”
Section: The Cell Cycle Is In Turn Regulated By Mitochondria Functionmentioning
confidence: 88%
“…Moreover, we have also shown that TBT results in growth arrest by targeting the glycolytic systems . Both mitochondrial fission and glycolysis have been reported to be linked to cell cycle alterations (Yamamori et al, 2015;Zhai et al, 2013). Thus, we are currently investigating whether TBT-induced mitochondrial fission or glycolytic inhibition are linked to G2/M cell cycle arrest or not.…”
Section: Discussionmentioning
confidence: 99%